Randomized trial protocol of interscalene nerve block vs liposomal bupivacaine injection after total shoulder arthroplasty. Issue 28 (10th July 2020) - He, Jianbin; Li, Yalan
Abstract: Background: The possibility of local infiltration analgesia (LIA) replacing interscalene blockade (ISB) as an integral component of a multimodal clinical pathway for total shoulder arthroplasty (TSA) needs to be further investigated. We thus further designed a randomized controlled study to compare LIA with ISB in the treatment of TSA. Methods: This blinded and randomised study was performed after approval of the institutional review board in the first affiliated hospital of Jinan University. The included patients were all aged over 18 years and underwent shoulder arthroplasty because of osteoarthritis of the shoulder. Subjects were randomized into 2 groups as follows: LIA or ISB. The primary outcome of this noninferiority study is opioid consumption within the first 24 hours following surgery. Secondary outcomes included pain scores, length of hospital stay, complication, and satisfaction score. P value < .05 was considered statistically significant. Results: For the present trial, we hypothesized that there would be no difference in pain score levels and opioid medication use throughout admission. Trial registration: This study protocol was registered in Research Registry (researchregistry5640).